Pengaruh Gaya Hidup dan Lingkungan dan Kebiasaan Masyarakat terhadap Penyebaran Malaria di Kampung Dosay Kabupaten Jayapura - Fitri Dia Muspitha; Swastika , I Ketut; Frengky Apay; Rumaseb, Ester (Pusat Riset dan Inovasi Nasional, 2025)
Malaria remains one of the major infectious diseases and continues to be a public health problem in many tropical regions, including Indonesia. This disease is transmitted through the bite of infected Anopheles mosquitoes and can have serious impacts on health, productivity, and quality of life. Jayapura Regency, particularly Dosay Village, is one of the malaria-endemic areas that requires serious attention in terms of control and prevention efforts. This study aimed to analyze the influence of lifestyle and environmental conditions on the spread of malaria in Dosay Village. A quantitative approach with a cross-sectional design was employed. The study sample consisted of 45 respondents selected using purposive sampling. Data were collected using a questionnaire that had been tested for validity and reliability, and analyzed using the chi-square test. The results showed a significant relationship between lifestyle and malaria transmission (p = 0.009), as well as between environmental conditions and malaria transmission (p = 0.002). These findings emphasize that community behaviors, such as using bed nets, maintaining household cleanliness, and avoiding outdoor activities at night, are closely associated with the risk of malaria transmission. Furthermore, environmental factors such as stagnant water, poor sanitation, and housing density also contribute significantly to the breeding of malaria vectors.